Seroprevalence of Immunoglobulins G and M Associated With Herpes Simplex Virus Type 2 among Apparently Healthy Individuals in Katsina State, Nigeria - Hayatudeen, M.R.; Mukhtar, G.L.; Aminu, M. (UMYU Journal of Microbiology Research)
Infection with Herpes Simplex Virus type 2 (HSV-2) is a significant public health problem being the leading cause of genital ulcerative disease. This study was aimed to evaluate the seroprevalence of herpes simplex virus type 2 among healthy individuals in Katsina State, and to determine the socio demographic and risk factors associated with HSV-2 infection in the study area. A cross-sectional serological survey enrolling 113 apparently healthy individuals from six Local Government Areas of Katsina State was conducted, to evaluate HSV-2 seroprevalence. Serum samples were obtained from randomly selected subjects. Samples were analysed using Immunoglobulins G (IgG) and M (IgM) HSV-2 specific commercial enzyme-linked immunosorbent assay kits. The overall seroprevalence of HSV-2 IgG and IgM was 71.7% and 32.7% respectively. HSV-2 seroprevalence increased with age. The results obtained demonstrated a high prevalence of HSV-2 seropositivity among apparently healthy individuals. We recommend educational awareness of Herpes type 2 infections among the populace and routine testing for Herpes type 2 antibodies in hospital laboratories to prevent HSV-2 related morbidity and mortality, particularly in apparently healthy individuals.